Objective TinyTimber : OTTO - Andersson, Lars; Lenschow, Oskar (My University, 2019)
When working as teaching assistants in the Real-time Systems courses on Chalmers, it was noticed that a significant amount of students find machine-oriented programming difficult to grasp. Therefore, the main purpose of this project has been to create an alternative way for students to understand the process of Real-time systems, by developing a new object-oriented language. This language is structured with classes and objects, much like Java and C++. It can be seen as a simplified, object-oriented version of the programming language C. In the development of the product, the language processing chain was followed, by utilizing tools like Flex and Bison. The resulting program, a transpiler, translates from the new language into the language C. This transpiler was integrated into CodeLite, which is the Integrated Development Environment (IDE) used in the labs. This integration was made to ensure easy usage. The finished product is beneficial for students who are more familiar with object-oriented programming, as they would not have to consider the machine-oriented aspects of the labs. Hence, this would increase the number of students understanding real-time systems, since they would face less obstacles during the course.
Keywords: C; Java; Object-Orientation; Programming; Real-time Systems; Transpiler; Flex; Bison